2014
DOI: 10.1074/jbc.m114.573857
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Identification-58 (CGI-58) Promotes Autophagy as a Putative Lysophosphatidylglycerol Acyltransferase

Abstract: Background: CGI-58 plays an essential role in lipid homeostasis with poorly defined mechanisms. Results: CGI-58 promotes autophagy as a novel lysophosphatidylglcyerol acyltransferase. Conclusion: CGI-58 regulates lipid homeostasis in part by promoting autophagy. Significance: Our findings provide potential molecular mechanisms by which CGI-58 mutations cause dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…It is important to note that other proteins have been mistakenly identified as LPAAT enzymes due to similar problems with affinity co-purification of bacterial LPAATs [107]. Another recent report also suggested that CGI-58 instead possesses intrinsic lysophosphatidylglycerol acyltransferase (LPGAT) activity to convert lysophosphatidylglycerols (LPG) to phosphatidylglycerol (PG) [108]. However, CGI-58 knockdown in mouse liver is associated with marked accumulation of PG lipids, which is inconsistent with a LPGAT activity for CGI-58 [41].…”
Section: Conclusion and Perspectives: The Continued Search For Amentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that other proteins have been mistakenly identified as LPAAT enzymes due to similar problems with affinity co-purification of bacterial LPAATs [107]. Another recent report also suggested that CGI-58 instead possesses intrinsic lysophosphatidylglycerol acyltransferase (LPGAT) activity to convert lysophosphatidylglycerols (LPG) to phosphatidylglycerol (PG) [108]. However, CGI-58 knockdown in mouse liver is associated with marked accumulation of PG lipids, which is inconsistent with a LPGAT activity for CGI-58 [41].…”
Section: Conclusion and Perspectives: The Continued Search For Amentioning
confidence: 99%
“…This work showed that CGI-58 competes for a caspase binding site on beclin 1, thereby blunting caspase-mediated cleavage of beclin 1, and also showed that CGI-58 and beclin 1 expression levels were correlated in human colorectal cancer tissue [94]. Another recent study showed that CGI-58 regulates the autophagy of mitochondria, a process known as “mitophagy” [108]. This study showed CGI-58 overexpression stimulated the activity of 5’-AMP-activated protein kinase (AMPK) and diminished the signaling of the mammalian target of rapamycin complex 1 (mTORC1), both of which are major regulatory nodes in autophagy activation [108].…”
Section: Conclusion and Perspectives: The Continued Search For Amentioning
confidence: 99%
See 1 more Smart Citation
“…An intrinsic lysophosphatidylglycerol acyltransferase (LPGAT) activity had been reported for murine ABHD5/ CGI-58 (70). However, this is currently under debate, as PGs are actually increased in hepatocytes of ABHD5 knockdown mice (28), and a more recent publication could not confirm this activity for mouse and plant ABHD5 (61).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have demonstrated that human CGI-58 has lysophosphatidic acid (LPA) acyltransferase (Ghosh et al, 2008a) and lysophosphatidylglycerol (LPG) acyltransferase (Zhang et al, 2014) activities. In various cancers, high levels of ABHD11 mRNA transcripts have been reported, but the role of this enzyme in cancer metabolism is not known.…”
mentioning
confidence: 99%